Electrocoagulation process for the treatment of metal-plating wastewater: Kinetic modeling and energy consumption - Ithan, Fatih; Ulucan-Altuntas, Kubra; Avsar, Yasar; Kurt, Ugur; Saral, Arstan (HIGHER EDUCATION PRESS, 2019)
It is known that wastewater produced by the metal-plating industry contains several heavy metals, which are acidic in nature and therefore toxic for the environment and for living creatures. In particular, heavy metals enter the food chain and accumulate in vital organs and cause serious illness. The precipitation of these metals is mostly achieved by pH adjustment, but as an alternative to this method, the electrocoagulation process has investigated in this study using iron and aluminum electrodes. The effects of the pH adjustment on removal before and after the electrocoagulation process were investigated, and cost analyses were also compared. It was observed that a high proportion of removal was obtained during the first minutes of the electrocoagulation process; thus, the current density did not have a great effect. In addition, the pH adjustment after the electrocoagulation process using iron electrodes, which are 10% more effective than aluminum electrodes, was found to be much more efficient than before the electrocoagulation process. In the process where kinetic modeling was applied, it was observed that the heavy metal removal mechanism was not solely due to the collapse of heavy metals at high pH values, and with this modeling, it was seen that this mechanism involved adsorption by iron and aluminum hydroxides formed during the electrocoagulation process. When comparing the ability of heavy metals to be adsorbed, the sequence was observed to be Cr>Cu>Ni>Zn, respectively. (c) Higher Education Press and Springer-Verlag GmbH Germany, part of Springer Nature 2019
Keywords: Electrochemical treatment; Heavy metals; Kinetic modeling; Pseudo first order kinetic; Pseudo second order kinetic; DRINKING-WATER; TOXICITY EVALUATION; REMOVAL; OPTIMIZATION; ADSORPTION; PARAMETERS; PHOSPHATE; ALUMINUM; ASSAY; Engineering; Environmental Sciences & Ecology